Is COVID-19 a threat or an opportunity for healthy eating? An exploration of the factors that moderate the impact of the pandemic on eating habits in Uruguay. (1st December 2021) - Vidal, Leticia; Brunet, Gerónimo; Curutchet, María Rosa; Girona, Alejandra; Pardiñas, Valeria; Guerra, Daniella; Platero, Estefanía; Machado, Lucía; González, Fernanda; Gugliucci, Vanessa; Ares, Gastón
Abstract: In May 2020, Uruguay was one of the few Latin American countries that had managed to control the outbreak of COVID-19 without mandatory curfews or quarantines. However, several social distancing measures created a major disruption in different aspects of the daily life of Uruguayan citizens. In this context, the objectives of the present work were i) to identify changes in eating habits perceived by Uruguayan citizens as a consequence of the COVID-19 pandemic, and ii) to explore factors associated with different perceived changes on eating habits. A cross-sectional online study was conducted with 891 participants, recruited using an advertisement on Facebook and Instagram. Fifty-one percent of the participants indicated that their eating habits had changed since the detection of the first cases of COVID-19 in Uruguay. Large heterogeneity in the categorization of the changes existed: 45% of the participants regarded the changes as positive, 32% as negative and 23% as neither positive nor negative. A multinomial logistic regression analysis was used to study the influence of explanatory variables in the likelihood of belonging to groups who reported different changes in eating habits (no changes, positive, negative, or neither positive nor negative changes). Household income and reliance on instrumental and emotional support increased the likelihood of reporting positive changes in eating habits, whereas negative changes were associated with a reduction in household income due to COVID-19 and the coping strategies self-distraction and self-blaming. Insights for policy making to reinforce positive effects and minimize threats to healthy eating are discussed.